ETHICAL DIFFERENCES BETWEEN SCIENCE AND PSEUDOSCIENCE - Farrukh Usmonov (Journal Park Publishing, 2023)
This article explores the interaction of science and ethics in modern society. The author examines the role of ethics in the scientific process and the problem of the moral justification of knowledge. Differences between scientific and non-linear knowledge are discussed from the point of view of ethical considerations. The article also highlights the external and internal types of relationships between science and ethics, as well as the impact of scientific knowledge on society and their social consequences. The author notes that modern science causes controversy and doubts, and at the same time it should serve the benefit of mankind. In conclusion, the article emphasizes the need for scientists to participate in resolving ethical issues related to scientific development, and calls for a conscious awareness of the relationship between truth and error
Keywords: science, ethics, society, social consequences, moral norms, responsibility, criteria of good and evil, distrust.